Metode Demonstrasi untuk Meningkatkan Pemahaman Santri Terhadap Materi Sholat - Saroh, May; Romdloni, Romdloni (JUPIN (Jurnal Pendidikan Islam Nusantara), 2023)
In education, every student has the right to achieve satisfactory academic performance. However, there are still differences in the level of understanding, both in terms of theoretical knowledge and practical skills. To support the success of non-formal education, such as a Quranic Education Center (TPQ), the application of effective teaching methods is needed to enhance students' understanding. One such method is the demonstration method. The aim of this research is to investigate the implementation of the demonstration method to improve students' understanding of prayer at TPQ Jami Bedilan. This study adopts a qualitative descriptive research design. Data collection was conducted through observation, interviews, and documentation. The research findings can be summarized as follows: (1) The implementation of the demonstration method for prayer at TPQ Jami Bedilan has been well executed, from the preparation stage to the final steps of the demonstration. However, there was one step that was not implemented, which was the lack of a trial activity conducted by the teacher. (2) The supporting factors and obstacles in the implementation of the demonstration method for prayer include the commitment of the educators, involvement of parents, and positive response from the students. On the other hand, the limiting factors arise from the educators themselves and the limited time available for teaching.